Penerapan Quality Function Deployment Untuk Meningkatkan EServequal (Implementation of Quality Function Deployment to Improve E-Servequal) - Handy Nur Cahya; Zuvita Sasa Dila (STIE Malangkucecwara, 2022)
This study aims to identify the service attributes of the application needed by consumers of the Pegadaian Digital Service application. The research objective can be completed using the Quality Function Deployment method which is able to define consumer needs into the company's technical response in improving the quality of application services. The use of the Quality Function Deployment method in this study resulted in eight variables of consumer needs. The need variable with the highest weight value will be the priority. The product variables that are prioritized are Features, Applications, and Servers. The three highest priority consumer needs can be met by the company by carrying out 4 of the 18 technical responses that have the highest importance weight. The Technical Responses were